2010
DOI: 10.4992/jjpsy.81.478
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the determinants of social withdrawal and affinity for social withdrawal

Abstract: This study examined the determinants of social withdrawal using data from a survey by the Tokyo Metropolitan Government Office for Youth Affairs and Public Safety (2008). In addition, this study identified young people who showed an affinity for social withdrawal although they were not in a state of withdrawal, and examined the determinants of an affinity for social withdrawal. The results of stepwise discriminant analysis showed that factors such as social phobia, depression, violence, and emotional bonds wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Participants were asked if each item applies to themselves and rated each item on a 4-point rating scale with the anchors ranging from 1 (no) to 4 (yes). We followed the instruction in the original Affinity of Hikikomori Scale (Watanabe et al, 2010) and did not clarify the period that participants were inquired about in the scale. Cronbach's alpha of the desire for hikikomori subscale and empathy for others with hikikomori subscale were .82 and .78 at Time 1, and .84 and .87 at Time 2, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were asked if each item applies to themselves and rated each item on a 4-point rating scale with the anchors ranging from 1 (no) to 4 (yes). We followed the instruction in the original Affinity of Hikikomori Scale (Watanabe et al, 2010) and did not clarify the period that participants were inquired about in the scale. Cronbach's alpha of the desire for hikikomori subscale and empathy for others with hikikomori subscale were .82 and .78 at Time 1, and .84 and .87 at Time 2, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It has been recently suggested that there are Japanese people that did not show prolonged social withdrawal but wanted to be withdrawn and had an empathetic attitude toward individuals with hikikomori. Watanabe et al (2010) named these desires and attitudes, the affinity for hikikomori, which were assessed by using a scale that was composed of four items including, "I didn't want to go out when an aversive event occurred" and "I can understand why some people stay in their home or rooms and cannot go out." The affinity for hikikomori in non-clinical university students was related to frequent absence from university classes and past experiences of school non-attendance from elementary, junior high, or high school (Shimono & Hasegawa, 2018;Shimono et al, 2020).…”
Section: ; English Translation Bymentioning
confidence: 99%
“…We developed the NEET/Hikikomori Risk (NHR) scale to measure the potential risk of becoming NH among young people. Previous studies have only examined NEET and Hikikomori as distinct categories with very few exceptions (Watanabe et al, 2010 ). With our scale, we identify psychological risk factors for NH for young people who are currently in some form of employment (including university students).…”
Section: Study 1: Developing the Nh Risk Scalementioning
confidence: 99%
“…The Cabinet Office of the Government of Japan (2010) developed the hikikomori symptoms scale consisting of four items (“I sometimes have in my mind an idea that I want to keep at home or in my room.”; “When bad things happen, I do not feel like I want to go outside.”; “I understand the feeling of people who keep in their room and do not go outside.”; and “I believe that keeping at home or in one’s room can be justified if there is a reason for it.”) 1 . An exploratory factor analysis conducted in a previous study revealed that these items load only on one construct (Watanabe et al, 2010). Maki, Kaita, and Yuzawa (2010) modified the scale from a 4-point Likert-type scale (1 = no ; 2 = maybe no ; 3 = maybe yes ; 4 = yes ) to a 6-point scale (1 = absolutely not true ; 6 = absolutely true ) to capture the diversity of the symptoms.…”
Section: Methodsmentioning
confidence: 95%
“…For example, in Hattori’s (2006) study, 100% of hikikomori patients stated that they were unable to show their identity to their parents for fear of rejection. Regarding nonclinical samples, young people with hikikomori symptoms were less likely to feel that their family is warm, to talk to their family members, and to feel that their family members love them and that their family is close to each other compared to those without hikikomori and hikikomori symptoms (Cabinet Office of the Japanese Government, 2010; Watanabe et al, 2010).…”
Section: Psychological Dysfunction In the Japanese Cultural Contextmentioning
confidence: 99%